2010
DOI: 10.1007/s11661-010-0394-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Pressure Torsion Processing and Annealing on Hydrogen Embrittlement of Type 304 Metastable Austenitic Stainless Steel

Abstract: The effect of high-pressure torsion (HPT) and annealing on hydrogen embrittlement (HE) of a type 304 stainless steel was studied by metallographic characterization and tensile test after hydrogen gas charging. A volume fraction of~78 pct of the austenite transformed to a¢ martensite by the HPT processing at an equivalent strain of~30. Annealing the HPT-processed specimen at a temperature of 873 K (600°C) for 0.5 hours decreased the a¢ martensite tõ 31 pct with the average grain size reduced to~0.43 lm through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…16) As for a 304 metastable austenitic steel, an ultrafine-grained twophase microstructure was produced through reversion of the deformation-induced martensite, which resulted in mitigation of the ductility loss due to both hydrogenation and ultra grain refinement. 17,18) This finding suggests that the presence of martensite prior to the hydrogenation may mitigate HE. Similar phenomena were observed in metastable austenitic steels with ordinary-sized grains.…”
Section: Introductionmentioning
confidence: 88%
“…16) As for a 304 metastable austenitic steel, an ultrafine-grained twophase microstructure was produced through reversion of the deformation-induced martensite, which resulted in mitigation of the ductility loss due to both hydrogenation and ultra grain refinement. 17,18) This finding suggests that the presence of martensite prior to the hydrogenation may mitigate HE. Similar phenomena were observed in metastable austenitic steels with ordinary-sized grains.…”
Section: Introductionmentioning
confidence: 88%
“…In the second stage, the strain-hardening exponent, n 1 , was~1.75 for the uncharged specimen and~0.94 for the hydrogencharged specimen ( Table I); both of these values were significantly higher than~0.4 for the millimeter-sized specimen not exhibiting the two-step strain hardening behavior. [13] Lee et al observed similar two-step strain hardening behavior in nitrogen-containing austenitic stainless steels and attributed the second stage strain hardening to the formation of a¢ martensite. [12] Based on this information, it is concluded that hydrogen hastened the onset of a¢ martensite formation, but it decreased the strain hardening rate after the transition strain, resulting in premature plastic instability.…”
mentioning
confidence: 92%
“…However, except for low stacking fault energy (SFE) austenitic steels such as high nitrogen-containing steels, [12] which exhibit significant hardening because of a¢ martensitic transformation, tensile straining at room temperature does not provide sufficient martensite formation to exhibit the two-step strain hardening behavior. [13,14] Micro-mechanical testing techniques have developed rapidly along with MEMS technology, and microtension testing has been applied to the analyses of mechanical characteristics on the scale of a few tens of micrometers. [15][16][17][18] If the specimen size is reduced to the scale of the region that the martensite covers entirely, i.e., a few tens of micrometers, the effects of the martensite formation on the strain hardening behavior can be revealed.…”
mentioning
confidence: 99%
See 2 more Smart Citations